2020
DOI: 10.1111/jocn.15261
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing speech recognition technology on the accuracy and efficiency (time to complete) clinical documentation by nurses: A systematic review

Abstract: Introduction Speech recognition technology (SRT) recognises an individual's spoken word signals through a microphone and subsequently processes the user's words into digital text by means of a computer. SRT remains well established and continues to grow in popularity among the various health disciplines. Many studies have been done to examine the effects of SRT on nursing documentation, however, no previous systematic review (SR) on the effects of SRT on accuracy and efficiency of nursing documentation was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Speech recognition technology can dramatically reduce the time required to write medical records for doctors and nurses by automatically inputting data in the medical records. It has been reported that this technology has reduced the burden and fatigue experienced by doctors and nurses and increased the time spent caring for patients [ 15 ]. In addition, conversational AI can be used to automate patient data collection as the SDS used in this study can collect important medical history and patient-reported outcomes.…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech recognition technology can dramatically reduce the time required to write medical records for doctors and nurses by automatically inputting data in the medical records. It has been reported that this technology has reduced the burden and fatigue experienced by doctors and nurses and increased the time spent caring for patients [ 15 ]. In addition, conversational AI can be used to automate patient data collection as the SDS used in this study can collect important medical history and patient-reported outcomes.…”
Section: Discusssionmentioning
confidence: 99%
“…In addition, conversational AI can be used to automate patient data collection as the SDS used in this study can collect important medical history and patient-reported outcomes. It can also be used for remote home monitoring [ 9 , 10 , 15 ].…”
Section: Discusssionmentioning
confidence: 99%
“…We are often called "open spoken English." With the development of speech recognition technology, the first question can be well evaluated by comparing and analyzing the examinee's pronunciation with the standard pronunciation [4], such as using the classical Goodness of Pronunciation (GOP) algorithm. In addition, it is necessary to comprehensively evaluate candidates' answers from multiple dimensions, for example, fluency, rhythm, intonation, richness of vocabulary, and meaning.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies can address specific existing problems: nurses spend at least thirty percent of their working day filling out forms and documenting patient data. Digitized documentation processes reduce paperwork, create optimized schedules, and increase productivity, allowing nurses more time for patient care [ 7 , 8 , 9 , 10 ]. Electronic medical records encourage health professionals’ exchange and decision-making [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%